Economic Factors Influencing Infrastructure Development in the Lao People's Democratic Republic - PHOMPADITH, soulidone; HER, Pheng; VATTHANA, Mongkhoun (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study analyzed the economic factors influencing infrastructure development in Lao PDR using time series data from 2000 to 2023. The data were obtained from the annual reports of the Bank of Lao PDR and analyzed using the Vector Error Correction Model (VECM). The results indicate that the public expenditure model and the foreign direct investment (FDI) model exhibit no cointegration effects. In contrast, the infrastructure development model, the official development assistance (ODA) model, and the trade volume model do show cointegration effects; however, only the infrastructure development model meets the criteria for a valid adjustment term coefficient. This model, which is central to the study, reveals that FDI has a small but positive short-term effect on infrastructure development—particularly on road network expansion. Nonetheless, during times of crisis, the model indicates that variables can adjust to long-term equilibrium by only 3.11%. Furthermore, the coefficient of infrastructure development in the cointegration equation is positive. In the long term, public expenditure positively influences infrastructure development, while FDI has a negative effect. These findings suggest that public expenditure and FDI have asymmetric long-term impacts on infrastructure development, operating in opposite directions.